2020
DOI: 10.1016/j.transci.2020.102848
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma from COVID 19 patients enhances intensive care unit survival rate. A preliminary report

Abstract: Convalescent plasma from COVID 19 patients enhances intensive care unit survival rate. A preliminary reportCoronavirus pandemic disease (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). At the time of this paper writing, over 2,5 million cases of COVID-19 have been reported, with more than 280,000 deaths all over the world. Italy is one of the first countries involved, with more than 200,000 reported infected people and 30,000 deaths. In the Basilicata south Italy region liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In our study, we examined the beneficial effect of CP in patients with severe COVID-19 using a matched propensity score analysis. This strategy has already been used in other trials, resulting in contradictory results [ 21 , 23 , 30 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 , 56 ]. In our study, the univariate analysis comparing the CP to the control group showed a significantly reduced risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we examined the beneficial effect of CP in patients with severe COVID-19 using a matched propensity score analysis. This strategy has already been used in other trials, resulting in contradictory results [ 21 , 23 , 30 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 , 56 ]. In our study, the univariate analysis comparing the CP to the control group showed a significantly reduced risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of individuals who have recovered from natural infection may help to determine how long antibodies persist after an immunizing exposure, and whether or not these antibodies might protect against re-infection. The persistence of antibody response may also help predict the efficacy of vaccines for COVID 19. COVID-19 convalescent plasma (CCP) is an investigational therapy that remains somewhat controversial, with conflicting reports of efficacy [3,4,5]. The underlying principle of this treatment approach is the passive transfer of anti-SARS-CoV-2 antibodies to patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 convalescent plasma (CCP) is an investigational therapy that remains somewhat controversial, with conflicting reports of efficacy [3, 4, 5]. The underlying principle of this treatment approach is the passive transfer of anti-SARS-CoV-2 antibodies to patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apart from the direct antibody (Ab)-mediated antiviral effect, CP contains anti-inflammatory cytokines, natural antibodies, and antimicrobial proteins such as defensins and pentraxins, which can control over-activation of the immune system and act in an immunomodulatory mode [ 15 ]. In the case of SARS-CoV-2 and in support of the beneficial use of CP, a recent meta-analysis showed that CP administration was associated with a significant reduction in mortality [ 16 ], whereas the transfusion of CP in 20,000 COVID-19 patients proved that it is safe and carries a very low risk of complications [ 17 ]. Nevertheless, in a most recent clinical trial, CP infusion in 228 COVID-19 patients with severe pneumonia did not offer any significant benefit as for clinical status and overall mortality rate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%